Feasibility and Efficacy of a Psychological Therapy for Patients With a Schizophrenic Psychosis in an Inpatient Setting: Study Protocol of a Randomized Switch Controlled Trial - Redlich Bossy, Mona; Mueller, Daniel; Seifritz, Erich; Vetter, Stefan; Egger, Stephan T. (Frontiers in Public Health, 2020)
Background: Schizophrenic psychoses are severe mental disorders. Despite advances in treatment, outcomes are still unsatisfying. The pharmacological treatments still show limitations regarding psychosocial functioning and neurocognitive impairment. In recent years new psychological therapies appeared, showing promising results. However, these interventions are mainly designed and studied for outpatients; their efficacy and feasibility for patients requiring hospitalization is still unknown. Therefore, we designed a clinical trial to compare a neurocognitive (Integrated Neurocognitive Treatment-INT); a cognitive-behavioural (Integrated Psychological Therapy-IPT); and a control (Cogpack) intervention for patients with a schizophrenic psychosis hospitalized for treatment. Methods: In a three-parallel-arm, single-blind, randomized, controlled study, we compare INT, IPT and Cogpack. Participants will undergo two weekly sessions of one intervention for at least 16 sessions. If due to randomization, participants were allocated in a treatment arm not suitable for them, they are allowed to switch the intervention after four sessions. Based on a sample size calculation, recruitment will continue until 30 participants complete the intervention for each treatment arm. Outcome Measurement: Primary outcome is change in symptom as measured by the Positive and Negative Syndrome Scale (PANSS); secondary outcomes are change in psychosocial functioning as assessed by the mini ICF-App and neurocognitive performance, assessed by the Matrics Cognitive Consensus Battery (MCCB). Other outcomes of interest are the Brief Symptom Inventory (BSI) and the Health of the Nation Outcome Scales (HoNOS); as well as prescribed medication, treatment retention and completion rates. Outcomes will be measured at baseline, after two weeks (before a potential switch of intervention arm), after completion of the treatment, as well a six and 12 months follow-up. Expected Outcomes: We expect an overall improvement; however, with differences in specific domains for each treatment arm, with those completing INT showing better outcomes than IPT and Cogpack, respectively. We expect low-functioning participants t drift to Cogpack and higher performance participants heading to INT. Conclusion: Due to the complexity of treatment for patients with a schizophrenic psychosis, it is crucial to compare different treatment options for those more severely affected and therefore requiring inpatient treatment.